Systematic Literature Review Metaverse 2019-2024, Ruang Lingkup, Potensi dan Tantangannya di Masa Depan - Yuli Fitrianto; Sindhu Rakasiwi (JSAI (Journal Scientific and Applied Informatics), 2024)
Although the metaverse is still a concept, the discussion continues to be carried out in line with the development of technology that leads to it and the latest products, such as the release of the Apple Vision Pro which is a hot topic of conversation in early 2024. Major world companies such as Apple, Facebook and Google look serious in welcoming this Metaverse. This Systematic Literature Review was carried out by extracting articles related to the Metaverse published between 2019 to 2024, which aims to determine the scope or field of development of Metaverse application related to the adoption of supporting technology, conclude what components can support the realization of the Metaverse, predict the potential and challenges that will be faced in the future, as well as submitting suggestions for future research.